Innovation of Smart Agricultural Control System in NFT Hydroponic based on Artificial Intelligence of Things - Nurjaya Nurjaya; Gema Aditya Mahendra; Indah Novi Yarman (Eduvest - Journal of Universal Studies, 2022)
Rapid population growth has had a significant effect on increasing food demand. However, the conversion of agricultural land to non-agricultural land cannot be avoided. Currently, there are only 8.1 million hectares of agricultural land and it is estimated that this will decrease to 5.1 million hectares of agricultural land by 2045. Hydroponic agriculture is one of the solutions for efficient use of agricultural land, one of which is the Hydroponic Nutrient Film Technique. That must be maintained and controlled are pH, Electrical Conductivity (EC), and flow. The optimum value of each parameter is pH 6, EC 5mS cm-1, and a flow of 1.5 l / m. However, the optimal value of each parameter will change with changing conditions and environment. As an innovative solution, the authors offer SANIC technology, a smart agricultural control system in NFT hydroponic based on artificial intelligence of things. The methodology used in this paper is ADDIE (Analysis, Design, Development, Implementation, and Evaluate). This technology has a multifunctional plant treatment that works automatically. The equipment is integrated with several components such as a pH sensor, Solenoid Valve, Flow Sensor and EC meter. The main system of this technology is controlled intelligently by Fuzzy Logic rules. This technology is also equipped with solar panels to support environmentally friendly energy needs.